A relação dos gastos em programas de assistência social com as variáveis macroeconômicas brasileiras - Senna, Viviane de (2015)
The Federal Constitution of 1988 was the first in Brazil to refer to social inequalities and social assistance as a public policy. Currently there are several programs that assist the population living in extreme poverty. Among the existing programs, the best known are the Bolsa Família Program and the Continued Benefit that have as their main task the transfer of minimum necessary income to families that fall within the pre-established criteria in specific Decrees and registered in the Unified Register for Programs social - CadÚnico. From the above, this study aims to examine the relationship between the main macroeconomic variables and spending on social welfare policy of the federal government in the period between January 2004 and August 2014. The methodology to be employed to achieve this goal is : the autoregressive moving average model with ARMAX exogenous variable, the Vector autoregression model - VAR, the Granger causality test, cointegration test Johansen and Error Correction Vector - VEC. The conclusions reached were positive for significant relationships between macroeconomic variables and social assistance programs, ie, programs influence the Brazilian economy.